2017
DOI: 10.1007/s11845-017-1651-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to COPD management guidelines in general practice? A review of the literature

Abstract: Current studies show significant variability in adherence to the GOLD guidelines. Barriers identified include lack of clarity, unfamiliarity with recommendations, and lack of familiarity with the guidelines. If general practice is expected to manage COPD and other chronic diseases, health service investment is needed to provide appropriate focused guidelines, to support their dissemination and resources to implement them in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…(Table 1S). A recent review including 11 studies performed in multiple countries across the globe showed a significant variability in the adherence rates to the GOLD PTGs [40]. For example, the pulmonologists' adherence rates to some other GOLD PTGs varied from 70.1% (Greece) [41] to 18.7% (USA) [7] ( Table 1S).…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 99%
“…(Table 1S). A recent review including 11 studies performed in multiple countries across the globe showed a significant variability in the adherence rates to the GOLD PTGs [40]. For example, the pulmonologists' adherence rates to some other GOLD PTGs varied from 70.1% (Greece) [41] to 18.7% (USA) [7] ( Table 1S).…”
Section: Discussion Of Results the Evaluation Of Pulmonologists'mentioning
confidence: 99%
“…Unfortunately, poor guideline adherence was frequently found in real-world practice in COPD. 23 The rate of guideline adherence for pulmonologists in Turkey was 59.5% according to the earlier 2006 GOLD report. 24 The guideline adherence rate was even lower for general practitioners (GPs) than for pulmonologists in Italy, 25 and the rate was as low as 8% for GPs in a Shanghai suburb.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent review found considerable variability among physicians' adherence to guideline recommendations, showing that the proportion of patients adequately prescribed ranged from 30% to 60%. 12 Data from a US cohort showed that appropriateness ranged from 30% to 45%. 4 A previous Italian study, held in the context of specialized lung clinics, found that only 37.9% of COPD patients were treated according to GOLD recommendations even though they were managed by specialized physicians.…”
Section: Discussionmentioning
confidence: 99%
“…At admission, 23.1% of them were treated with at least 1 LABA and 24.2% were treated with at least 1 LAMA. Regarding the association of [2][3][4][5][6][7][8][9][10][11][12][13][14] .001 Education, y (n ¼ 5523) 5 [5][6][7][8][9] 5 [5][6][7][8] . Table S2).…”
Section: Pharmacologic Treatment and Therapeutic Appropriatenessmentioning
confidence: 99%
See 1 more Smart Citation